2016
DOI: 10.1097/md.0000000000003248
|View full text |Cite
|
Sign up to set email alerts
|

Combination of PLR, MLR, MWR, and Tumor Size Could Significantly Increase the Prognostic Value for Gastrointestinal Stromal Tumors

Abstract: Systemic inflammation and immune response were associated with prognosis of tumors. However, data was limited due to the relatively low incidence of gastrointestinal stromal tumors (GISTs). The aim of the present study was to investigate the predictive value of preoperative peripheral blood cells in prognosis of GISTs.From September 2008 to July 2015, a total of 274 GIST patients in our department were enrolled in the present study. Clinicopathological features of GISTs were recorded. The association between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 34 publications
(38 reference statements)
4
43
2
1
Order By: Relevance
“…Perez et al first showed that a high level of NLR was correlated with poor prognosis, followed by Kargin et al, Goh et al, Stotz et al, and Feng et al On the other hand, the sixth study on this topic by Racz et al, did not find an association between NLR and recurrence, but between PLR and DFS. PLR was associated with DFS also by Stotz et al, Goh et al, and Feng et al. Feng et al added MLR, NWR, MWR, and LWR to the analysis of NLR and PLR, and obtained an association between all of them and DFS on univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Perez et al first showed that a high level of NLR was correlated with poor prognosis, followed by Kargin et al, Goh et al, Stotz et al, and Feng et al On the other hand, the sixth study on this topic by Racz et al, did not find an association between NLR and recurrence, but between PLR and DFS. PLR was associated with DFS also by Stotz et al, Goh et al, and Feng et al. Feng et al added MLR, NWR, MWR, and LWR to the analysis of NLR and PLR, and obtained an association between all of them and DFS on univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocytosis and a high number of tumor‐infiltrating lymphocytes were associated with improved prognosis and a better response to cytotoxic treatment in a variety of cancers . The combination of lymphocytopenia and neutrophilia may reflect an inflammatory status where the high neutrophil count suppresses the cytolytic activity of lymphocytes, T cells, and NK cells …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations